Realizing a High‐Performance Na‐Storage Cathode by Tailoring Ultrasmall Na2FePO4F Nanoparticles with Facilitated Reaction Kinetics. Issue 13 (7th May 2019) - Wang, Fanfan; Zhang, Ning; Zhao, Xudong; Wang, Lixuan; Zhang, Jian; Wang, Tianshi; Liu, Fanfan; Liu, Yongchang; Fan, Li‐Zhen
Abstract: In this paper, the synthesis of ultrasmall Na2 FePO4 F nanoparticles (≈3.8 nm) delicately embedded in porous N‐doped carbon nanofibers (denoted as Na2 FePO4 F@C) by electrospinning is reported. The as‐prepared Na2 FePO4 F@C fiber film tightly adherent on aluminum foil features great flexibility and is directly used as binder‐free cathode for sodium‐ion batteries, exhibiting admirable electrochemical performance with high reversible capacity (117.8 mAh g −1 at 0.1 C), outstanding rate capability (46.4 mAh g −1 at 20 C), and unprecedentedly high cyclic stability (85% capacity retention after 2000 cycles). The reaction kinetics and mechanism are explored by a combination study of cyclic voltammetry, ex situ structure/valence analyses, and first‐principles computations, revealing the highly reversible phase transformation of Na2 Fe II PO4 F ↔ NaFe III PO4 F, the facilitated Na + diffusion dynamics with low energy barriers, and the desirable pseudocapacitive behavior for fast charge storage. Pouch‐type Na‐ion full batteries are also assembled employing the Na2 FePO4 F@C nanofibers cathode and the carbon nanofibers anode, demonstrating a promising energy density of 135.8 Wh kg −1 and a high capacity retention of 84.5% over 200 cycles. The distinctive network architecture of ultrafine active materials encapsulated into interlinked carbon nanofibers offers an ideal platform for enhancing the electrochemical reactivity, electronic/ionic transmittability, and structural stability of Na‐storage electrodes. Abstract : Ultrasmall Na2 FePO4 F nanograins (≈3.8 nm) uniformly embedded in porous N‐doped carbon nanofibers are synthesized by electrospinning, and the obtained Na2 FePO4 F@C fiber membrane tightly adhered to aluminum foil is directly adopted as binder‐free cathode for sodium‐ion batteries. Upon repetitive sodiation/desodiation, a highly reversible phase transition of Na2 Fe II PO4 F ↔ NaFe III PO4 F with facilitated reaction kinetics is demonstrated, enabling admirable electrochemical performance.